2020
DOI: 10.2139/ssrn.3647298
|View full text |Cite
|
Sign up to set email alerts
|

The Early Impact of COVID-19 on Local Commerce: Changes in Spend Across Neighborhoods and Online

Abstract: We document a number of striking features about the initial impact of the pandemic on local commerce across 16 US cities. There are two novel contributions from this analysis: exploration of neighborhood-level effects and shifts between offline and online purchasing channels. In our analysis we use approximately 450 million credit card transactions per month from a rolling sample of 11 million anonymized customers between October 2019 and March 2020. Across the 16 cities we profile, consumers decreased spend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
3
9
0
1
Order By: Relevance
“…The results based on online versus offline shopping show that online shopping has increased by up to 21%, while its expenditure share has increased by up to 16% compared to the pre-COVID-19 period. These results are consistent with those in Relihan et al (2020) who have used an earlier version of the dataset used in this paper and shown that the increase in online shopping has been only about 1.5% in March 2020 (with respect to March 2019). Nevertheless, different from Relihan et al (2020) who have focused on aggregate-level data in the U.S. to obtain this measure, this paper has shown that, after controlling for factors that are zip-code and time specific as well as those that are zip-code and sector specific, the common factor across zip codes representing online spending within the U.S. has increased by about 7.4% in March 2020 (with respect to March 2019).…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results based on online versus offline shopping show that online shopping has increased by up to 21%, while its expenditure share has increased by up to 16% compared to the pre-COVID-19 period. These results are consistent with those in Relihan et al (2020) who have used an earlier version of the dataset used in this paper and shown that the increase in online shopping has been only about 1.5% in March 2020 (with respect to March 2019). Nevertheless, different from Relihan et al (2020) who have focused on aggregate-level data in the U.S. to obtain this measure, this paper has shown that, after controlling for factors that are zip-code and time specific as well as those that are zip-code and sector specific, the common factor across zip codes representing online spending within the U.S. has increased by about 7.4% in March 2020 (with respect to March 2019).…”
Section: Introductionsupporting
confidence: 92%
“…These results are consistent with those in Relihan et al (2020) who have used an earlier version of the dataset used in this paper and shown that the increase in online shopping has been only about 1.5% in March 2020 (with respect to March 2019). Nevertheless, different from Relihan et al (2020) who have focused on aggregate-level data in the U.S. to obtain this measure, this paper has shown that, after controlling for factors that are zip-code and time specific as well as those that are zip-code and sector specific, the common factor across zip codes representing online spending within the U.S. has increased by about 7.4% in March 2020 (with respect to March 2019). This difference can again be attributed to estimating common factor across zip codes in this paper as opposed to using aggregate-level data.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…With lowincomes, limited private automobile access, reliance on public transit for commuting over long distances, and the rapid spread of COVID-19 infections across Detroit, there was a severe overall impact on accessing stores, and this was reflected in local commercial spending. Following the COVID-19 outbreak, the City of Detroit confronted the fourth sharpest decline among major U.S. cities in local shopping, behind San Francisco, Chicago and New York, reflective, in part, on the overall mobility, sociodemographic composition, and health vulnerabilities of the population [57].…”
Section: Discussionmentioning
confidence: 99%